Between Army, Society, and Law: Addressing the Personal Problems of Reservists in the Yom Kippur War (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
October 6, 1973 - the day on which the Yom Kippur War broke out - is etched in Israeli national memory. The day on which the war ended and its outcomes are equally familiar. After three weeks of fierce and determined fighting, Israel thwarted the coordinated attack and launched counteroffensives that forced Egypt and Syria to agree to ceasefire agreements on October 24, 1973. Contrary to public perception, the ceasefire did not end the war completely. Maintaining the separation-of-forces agreements with Egypt and Syria required large numbers of troops, hastily mobilized in early October, to remain in service for many more months. Of the 260,000 soldiers mobilized at the height of the war, approximately 190,000 were still in the army in mid-November, creating a significant social and economic burden on Israel. Apart from being on active military duty and having to maintain a constant state of alert, reservists faced hardships in their civilian lives as a result of their unexpected and prolonged military service.This article examines the central role of the reserve army in Israeli security doctrine. It analyzes how reservists’ problems were addressed during the Yom Kippur War through the assistance mechanism for reserve soldiers established within the Military Advocate General’s department in January 1974. By examining the legal and practical response to reservists’ difficulties, I shed light on a lesser-known aspect of civil-military relations in Israel and illustrate the importance of addressing the individual reservist as part of the effort to strengthen social resilience – one of the cornerstones of Israel’s security doctrine.
Keywords: civil-military relations; Israeli security doctrine; Military Advocate General; reserve service; Yom Kippur War; Emergency Time Extensions Law